Profiles of Students' Logical-Mathematical Reasoning in Statistical Physics Learning: Differentiated Learning and Computer Simulation Perspectives - Asbanu, Dens E. S. I.; Yustiana, Yusi Riksa; Sinaga, Parlindungan; Virijai, Febrian (Universitas Muhammadiyah Purworejo, 2026)
This study aims to analyze the logical-mathematical thinking ability of prospective physics teacher students as a basis for designing learning strategies based on differentiated learning and computer simulation. The survey method involved 37 physics education study program students from one of the universities on the island of Timor. Data was collected through a logical thinking ability test covering five main types of reasoning: proportional, variable control, probability, correlation, and combinatorial. The analysis results showed that most students were at the level of transitional logical thinking (70 percent), while only 11 percent reached the formal level. The chi-squared test showed a significant relationship between the semester level and students' logical thinking ability. These results show the need for learning that supports the transition from concrete and transitional thinking to formal. Implementing computer simulation in statistical physics learning is recommended to improve students' logical-mathematical thinking skills, support the understanding of abstract concepts, and facilitate the success of complex physics learning.